Factors affecting the readiness for hospital discharge of initially treated pulmonary tuberculosis patients in China: a phenomenological study - Jiani Wang; Yuan Zhang; Qin Rao; Chenhuan Liu; Hengxu Du; Xiaohua Cao; Mingxia Xi (BMC, 2024)
Abstract Background Despite readiness for hospital discharge widespread popularity since readiness for hospital discharge introduction in 1979 and extensive study, readiness for hospital discharge among pulmonary tuberculosis (PTB) patients has not yet been investigated. Moreover, the factors influencing this process remain unclear. Objective The objective of this study was to investigate the factors influencing readiness for hospital discharge in initially treated PTB patients using the capability, opportunity, motivation-behavior (COM-B) model. Methods This phenomenological study was conducted from December 2023 to March 2024. Face-to-face individual interviews were conducted with 18 initially treated patients with PTB according to a semistructured interview guide developed on the basis of the COM-B model. The interview data were subjected to analysis using NVivo 14 software and Colaizzi's method. Results As a result, 6 themes and 14 subthemes were identified. Physical capability for readiness for hospital discharge (subthemes included poor health status, early acquisition of adequate knowledge about PTB, inadequate knowledge about readiness for hospital discharge), psychological capability for readiness for hospital discharge(subthemes included false perceptions about readiness for hospital discharge, high treatment adherence), physical opportunity for readiness for hospital discharge (subthemes included high continuity of transition healthcare, insufficient financial support, insufficient informational support), social opportunity for readiness for hospital discharge (subthemes included stigmatization, inadequate emotional support), reflective motivation for readiness for hospital discharge (subthemes included lack of reflection on coping with difficulties, intention to develop a readiness for hospital discharge plan), and automatic motivation for readiness for hospital discharge (subthemes included strong desire to be cured, negative emotions). Conclusion We established factors related to readiness for hospital discharge in initially treated PTB patients in terms of capability, opportunity and motivation, which can inform the future development of readiness for hospital discharge plans. To improve patients' readiness for hospital discharge, patients need to be motivated to plan and desire readiness for hospital discharge, patients' knowledge and treatment adherence should be improved, and patients' transition healthcare continuity and emotional support should be focused on. Moreover, the quality of readiness for hospital discharge and discharge education should be assessed in a timely manner to identify impeding factors and provide interventions.